2020
DOI: 10.3389/fphar.2020.00421
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Exerts Cognitive Benefits and Promotes Hippocampal Neurogenesis in Stroke Mice by Downregulating Interleukin-17 Expression via Wnt Pathway

Abstract: Background: Stroke remains a leading cause of adult disability and the demand for stroke rehabilitation services is growing, and Astragaloside IV (As IV), a primary bioactive compound of Radix Astragali: Astragalus mongholicus Bunge (Fabaceae), may be a promising stroke therapy. Methods: To access the effect of As IV on adult mice after ischemic stroke, a photochemical ischemia model was established on C57BL/6 mice, which were intravenously administered As IV for three consecutive days later. And then the cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…In our previous study, As-IV exerts cognitive benefits and promotes hippocampal neurogenesis and synaptic plasticity in stroke mice via Wnt pathway. IL-17 expression is downregulated by administering As-IV 29 , which is consistent with the results in other acute diseases [30][31][32] . Therefore, it seems that As IV could be a promising strategy in the therapeutic arsenal against ischemic cortex after stroke for its effect on activating proliferation and promoting neurogenesis.…”
Section: Introductionsupporting
confidence: 90%
“…In our previous study, As-IV exerts cognitive benefits and promotes hippocampal neurogenesis and synaptic plasticity in stroke mice via Wnt pathway. IL-17 expression is downregulated by administering As-IV 29 , which is consistent with the results in other acute diseases [30][31][32] . Therefore, it seems that As IV could be a promising strategy in the therapeutic arsenal against ischemic cortex after stroke for its effect on activating proliferation and promoting neurogenesis.…”
Section: Introductionsupporting
confidence: 90%
“…Indeed, previous studies have demonstrated the inhibitory effect of IL-17 on neurogenesis, in particular, on neural progenitor proliferation in vivo and in vitro [23,34,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…The rats were randomly (simple randomization with computer‐generated random numbers) divided into different experimental groups. No sample calculation was performed in advance, and the sample sizes were based on previous studies (Sun et al., 2020; Wang et al., 2020). Before the IFS procedure, all rats were conducted with 1‐week adaptation for the new environment.…”
Section: Methodsmentioning
confidence: 99%